Is cystic artery lymph node excision during laparoscopic cholecystectomy a marker of technique?. Issue 6 (1st July 2017) - Wysocki, Arkadiusz P.; Murphy, Skyle; Ware, Robert S.
Abstract : Background: In order to minimize bile duct injury, experts suggest that dissection during laparoscopic cholecystectomy (LC) should be performed lateral to the lymph node (LN). This study aims to determine whether the frequency of excision of the LN is related to patient factors, disease severity or surgical difficulty. Methods: All LCs performed or supervised by one surgeon were identified from a prospective database. The presence of LN was retrospectively determined by reviewing the gallbladder histology report. Results: The LN was identified in 10.4% of 1332 cholecystectomies. The American Society of Anesthesiologists class 3 was associated with a lower rate of LN excision compared with class 1 (odds ratio: 0.36; P = 0.049) as was the presence of a senior surgical trainee (odds ratio: 0.18; P < 0.001). Rate of LN excision was independent of patient demographic and clinical characteristics, including indication for cholecystectomy, conversion to open, gallbladder perforation, cholangiography, bile duct exploration and overall surgical difficulty. Conclusions: The frequency with which the LN is excised during LC by the one surgeon is independent of the majority of clinical and surgical factors and may represent a surrogate marker of surgical technique. Whether this is related to the rate of bile duct injury remains to be determined.